Design and Development of a Smart Mirror Using Raspberry Pi - Gangal, Bharat (Journal of Advanced Research in Information Technology, Systems and Management; Vol 4 No 1 (2020): Journal of Advanced Research in Information Technology, Systems & Management, 2021)
This paper describes the designing and implementation of a”Smart Mirror Using Raspberry Pi”. The device that works as a digital display showing the contents such as time, date, weather and news simultaneously. The user can interact with the mirror by giving commands to it, so it can also be referred as an interactive display. It has various applications like displaying real time information updates and appliances control. How to cIte thIs artIcle: Manglani T, Mukherjee D, Gangal B et al. Smart Mirror Design and Development By Raspberry Pi. J Adv Res Info Tech Sys Mgmt 2020; 4(1). 1-4.